Evaluation of Visual Localization Systems in Underground Mining - Kanellakis, Christoforos; Nikolakopoulos, George (2016 24th Mediterranean Conference on Control and Automation (MED), 2016)
In this article an evaluation of the current technology on visual localization systems for underground mining is presented. The proposed study is considered to be the first step among others towards enabling the vision of underground localization for Unmanned Micro Aerial Vehicles. Furthermore, the aim of this article, is to verify applicable and reliable low cost existing methods and technologies for the problem of UAV localization in underground, harsh mining environments and more specifically in one of the biggest mines in Europe, the iron ore mine of LKAB in Kiruna, Sweden. In the experimental trials, the sensors employed were a RGB-D camera, a Kinect 2 and a Playstation 3 Eye web camera used in two configurations, as a stereo rig and as a monocular visual sensor. The processing of the stored data from the experiments will provide an insight for the applicability of these sensors, while it will identify what further technological and research developments are required in order to develop affordable autonomous UAV solutions for improving the underground mining production processes. Godkänd; 2016; 20160419 (geonik) Collaborative Aerial Robotic Workers, AEROWORKS